Novel incorporation of redox active organic molecule with activated carbon as efficient active material of supercapacitors. (September 2022) - Kuo, Tsung-Rong; Lin, Lu-Yin; Kubendhiran, Subbiramaniyan; Li, Yi-Chiun; Chung, Ren-Jei; Yougbaré, Sibidou
Abstract: Activated carbon (AC) is intensively applied as active material of supercapacitor (SC) due to high porosity and surface area. Incorporating battery-type materials in AC can enhance energy storage ability by generating redox reactions, but poor cycling stability of battery-type materials limits practical use of SC. Similar surface properties can be achieved by redox active organic compounds, which also possesses rich functional groups with extra redox ability. Unlike battery-type materials producing redox reactions from transition metals, incorporating organic molecule is expected to generate redox reactions without reducing cycling stability of AC. In this study, it is the first time to fabricate 1, 4 benzene diboronic acid (DBA) and AC composite (DBA-AC) as active material of SC. The ratio of DBA and AC is optimized regarding to uniformity of DBA decoration. The optimized DBA-AC electrode presents a specific capacitance (CF ) of 211.4 F/g at 20 mV/s, owing to the largest surface area and abundant functional groups. A flexible symmetric SC based on the optimized DBA-AC electrodes shows the maximum energy density of 0.761 Wh/kg at the power density of 400 W/kg. The CF retention of 110% and Coulombic efficiency higher than 95% after 10, 000 times charge and discharge cycling process are also achieved. Graphical abstract: Unlabelled Image Highlights: Adding organics in activated carbon generates redox reaction and maintains stability. 1, 4 Benzene diboronic acid and activated carbon composite (DBA-AC) is synthesized. DBA and AC ratio in composite is optimized as active material of supercapacitor (SC). The optimized DBA-AC electrode shows specific capacitance of 211.4 F/g at 20 mV/s. Capacitance retention of 110% and Coulombic efficiency of 95% are got in 10, 000 cycle.